In vitro effects of arachidonic acid and docosahexaenoic acid on osteoclastogenesis and bone resorption in human CD14+ monocytes - Coetzee, Magdalena (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2015.